Relationship Between Organizational Commitment and Employee Satisfaction of PT X - Alif Hiola, Adnan; Hanurawan, Fattah (KnE Social Sciences, 2022)
This research aims to examine the relationship between job satisfaction and organizational commitment in employees of PT X. This study used quantitative research with a correlational research design. The research population were all the employees of PT X, 34 employees in total The sampling technique used is saturated sampling. The data collection method used is the adaptation of the Organizational Commitment Scale (OCS) and the generic job satisfaction scale with the validity used in this study is a validity construct. The data analysis technique used in this research is product-moment correlation. The results of the hypothesis test show that the organizational commitment of most of the employees of PT X is in very high classification, the job satisfaction of most of the employees of PT X is included in the high classification, and the positive relationship of employees of PT X between organizational commitment and job satisfaction. The author hopes that further researchers will make this research a valid reference for future research. And the authors suggest to develop this research. Keywords: organizational commitment, employee, statisfaction